Cytomolecular Analysis of Ribosomal DNA Evolution in a Natural Allotetraploid Brachypodium hybridum and Its Putative Ancestors—Dissecting Complex Repetitive Structure of Intergenic Spacers - Borowska-Zuchowska, Natalia; Kwasniewski, Miroslaw; Hasterok, Robert (Frontiers in Plant Science, 2016)
Nucleolar dominance is an epigenetic phenomenon associated with nuclear 35S rRNA genes and consists in selective suppression of gene loci inherited from one of the progenitors in the allopolyploid. Our understanding of the exact mechanisms that determine this process is still fragmentary, especially in case of the grass species. This study aimed to shed some light on the molecular basis of this genome-specific inactivation of 35S rDNA loci in an allotetraploid Brachypodium hybridum (2n=30), which arose from the interspecific hybridization between two diploid ancestors that were very similar to modern B. distachyon (2n=10) and B. stacei (2n=20). Using fluorescence in situ hybridization with 25S rDNA and chromosome-specific BAC clones as probes we revealed that the nucleolar dominance is present not only in meristematic root-tip cells but also in differentiated cell fraction of B. hybridum. Additionally, the intergenic spacers (IGSs) from both of the putative ancestors and the allotetraploid were sequenced and analyzed. The presumptive transcription initiation sites, spacer promoters and repeated elements were identified within the IGSs. Two different length variants, 2.3 kb and 3.5 kb, of IGSs were identified in B. distachyon and B. stacei, respectively, however only the IGS that had originated from B. distachyon-like ancestor was present in the allotetraploid. The amplification pattern of B. hybridum IGSs suggests that some genetic changes occurred in inactive B. stacei-like rDNA loci during the evolution of the allotetraploid. We hypothesize that their preferential silencing is an effect of structural changes in the sequence rather than just the result of the sole inactivation at the epigenetic level.